2008
DOI: 10.1089/cpt.2007.0518
|View full text |Cite
|
Sign up to set email alerts
|

Cryopreservation of Brown Bear Skin Biopsies

Abstract: Genetic resource banks and assisted reproductive technologies support the conservation of endangered or threatened species. In this study we assessed two procedures to cryopreserve skin biopsies from live brown bears. Skin biopsies were taken from six live, anesthetized brown bears. Single biopsies (n ‫؍‬ 3) of each animal were cut into small pieces and assigned to one of the three experimental groups: freezing, vitrification, or untreated fresh. There were no differences on cell attachment. However, both free… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 11 publications
0
4
0
1
Order By: Relevance
“…Nevertheless, the alteration in the other parameters of tissues cryopreserved by SSV may have been caused by high concentrations of cryoprotectants. In a study by Caamaño et al (2008), vitrification showed lower efficiency compared to SF and noncryopreserved tissues derived from brown bears ( Ursus arctos ), suggesting that high concentrations of cryoprotectants affect the quality of vitrified tissues. Additionally, other factors may influence the efficiency of the SSV, such as the use of a pre‐equilibration solution/step, tissue type (Caputcu et al, 2013), tissue thickness (Carvalho et al, 2013), warming and reanimation conditions (Lima et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, the alteration in the other parameters of tissues cryopreserved by SSV may have been caused by high concentrations of cryoprotectants. In a study by Caamaño et al (2008), vitrification showed lower efficiency compared to SF and noncryopreserved tissues derived from brown bears ( Ursus arctos ), suggesting that high concentrations of cryoprotectants affect the quality of vitrified tissues. Additionally, other factors may influence the efficiency of the SSV, such as the use of a pre‐equilibration solution/step, tissue type (Caputcu et al, 2013), tissue thickness (Carvalho et al, 2013), warming and reanimation conditions (Lima et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the alteration in the other parameters of tissues cryopreserved by SSV may have been caused by high concentrations of cryoprotectants. In a study by Caamaño et al (2008), vitrification showed lower efficiency compared to SF and noncryopreserved tissues derived from brown bears (Ursus arctos),…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Assim, como técnicas de conservação de tecidos somáticos usadas em mamíferos silvestres, têm-se a criopreservação por congelação lenta (Caamaño et al, 2008), por vitrificação (Borges et al, 2017) e a refrigeração (Queiroz Neta et al, 2018). Esta última tem sido empregada especialmente para o transporte ou conservação em curto prazo de tecidos somáticos de indivíduos localizados em regiões de difícil acesso ou distantes dos laboratórios especializados (Tovar et al, 2008).…”
Section: Introductionunclassified
“…For all these applications, attention to the establishment of biobanks using the skin, especially for species threatened with extinction, has increased in recent years (Tunstall et al, ), as the skin provides a greater recovery of the genetic diversity of the population regardless of gender and age of the individual (León‐Quinto et al, ). In this sense, somatic banks using the skin have been implemented in some wild species of endangered felids, such as the Iberian lynx ( Lynx pardinus , León‐Quinto et al, ), marbled cats ( Pardofelis marmorata ) and flat‐headed cats ( Prionailurus planiceps , Thongphakedee et al, ), as well other wild mammals such as the brown bear ( Ursus arctos , Caamaño et al, ) and collared peccaries ( Pecari tajacu , Borges, Lima, et al, ).…”
Section: Introductionmentioning
confidence: 99%